Pemanfaatan Lahan dan Penyemaian Bibit Tanaman Obat Keluarga (TOGA) Menuju Keluarga Sehat pada Ibu Pemberdayaan Kesejahteraan Keluarga (PKK) - Anggriyani, Farida Catur Wahyu; Sari, Sri Wulan; Asnidar, Asnidar (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The current development of plants that have medicinal properties has progressed, where the discovery of drugs and new sophisticated technologies have become alternative solutions in the advancement of the pharmaceutical world. Utilizing yards which are generally not well utilized has many advantages, especially in terms of increasing family income, for example as living barns and living pharmacies, so they need to be developed intensively. Simple technology that must be implemented can bring broad benefits to society, not only in the process of food independence but can also be directed towards health independence through the development of Family Medicinal Plants (TOGA). TOGA is synonymous with herbal medicine where the raw materials for making herbal medicine are dominated by a bitter taste, have no aesthetic value and are rarely consumed by the public. This makes it difficult to develop the value of family medicinal plants. This community service aims to find out and understand the community's background in understanding the background of TOGA, how to plant TOGA plants, and how to use them to revitalize the TOGA program, especially in Teuk Pandan Village. This service activity then carried out activities on how to plant TOGA plants properly and correctly as well as providing several family medicinal plants which would be planted in the yard of the Village TOGA post. From this community service activity it can be concluded that there is a lack of public knowledge in knowing the types of TOGA plants and the benefits of various TOGA plants as well as minimal use of the limited land owned by residents.